Detecting TCP SYN flood attack based on anomaly detection - Siti Hajar, C. Haris; R. Badlishah, Ahmad Dr.; Mohd Alif Hasmani, Abd Ghani (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/